How do you find the antiderivative of #e^(2x)(sin x)#?

Answer 1

#inte^(2x)sinxdx=1/5e^(2x)(2sinx-cosx)+C#

#I=inte^(2x)sinxdx#
We should try integration by parts. Typically when assigning values of #u# and #dv#, we want to choose a function for #u# that will get simpler as we differentiate it. However, we see that #e^(2x)# will stay being an exponential function and #sinx# will bounce back and forth through trigonometric functions.
In fact, we see it doesn't really matter which we choose for #u# and which for #dv#. On a whim, let:
#{(u=e^(2x),=>,du=2e^(2x)dx),(dv=sinxdx,=>,v=-cosx):}#

Then:

#I=uv-intvdu#
#I=-e^(2x)cosx-int(-cosx)(2e^(2x)dx)#
#I=-e^(2x)cosx+2inte^(2x)cosxdx#
Perform integration by parts once more. Again choose #e^(2x)# as #u#.
#{(u=e^(2x),=>,du=2e^(2x)dx),(dv=cosxdx,=>,v=sinx):}#
#I=-e^(2x)cosx+2[uv-intvdu]#
#I=-e^(2x)cosx+2uv-2intvdu#
#I=-e^(2x)cosx+2e^(2x)sinx-2intsinx(2e^(2x)dx)#
#I=-e^(2x)cosx+2e^(2x)sinx-4inte^(2x)sinxdx#

Observe that both sides of the equation now contain the integral we began with, allowing us to write:

#I=-e^(2x)cosx+2e^(2x)sinx-4I#
Solve for #I# treating the entire integral like we would any other variable:
#5I=-e^(2x)cosx+2e^(2x)sinx#
#5I=e^(2x)(2sinx-cosx)#
#I=1/5e^(2x)(2sinx-cosx)#
#inte^(2x)sinxdx=1/5e^(2x)(2sinx-cosx)*C#
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

# int \ e^(2x)sin(x) \ dx = e^(2x)(2/5sinx- 1/5cosx) + c#

An alternative method for handling form integrals is as follows:

# I_1 = int \ e^(ax)sin(omega x) \ \ #, or # \ \ I_2 = int \ e^(ax)cos(omega x) #

is to determine the solution's form by applying some intuition.

Irrespective of the trig function, the results are analogous, so wlog let us consider only #I_1#. If we use Integration by parts we find that we can decompose #I_1# as follows:
# I_1 = A_1e^(ax)cos(omega x) + A_2 \ int \ e^(ax)cos(omega x) #

which is not very helpful until we use Integration By Parts twice, providing:

# I_1 = A_4e^(ax)sin(omega x) + A_5e^(ax)cos(omega x) + A_6 \ int \ e^(ax)sin(omega x) #

Or:

# I_1 = A_4e^(ax)sin(omega x) + A_5e^(ax)cos(omega x) + A_6 I_1 #
Which is now an algebraic equation which can be solved for #I_1#
# I_1 = e^(ax)(A_7sin(omega x) + A_8cos(omega x)) #

With this knowledge, we can begin by making the following assumption about the integral result and then differentiate it to see if it works:

Assume the following solution:

# y= e^(2x)(Asinx + Bcosx)#
Differentiating wrt #x# and applying the product rule we get:
# dy/dx = e^(2x)(Acosx-Bsinx) + 2e^(2x)(Asinx + Bcosx)# # " " = e^(2x)((A+2B)cosx+(2A-B)sinx) #
We want #dy/dx = e^(2x)sinx#, so equating coefficients of sine and cosine we get:
# cosx: \ A+2B=0 # # sinx: \ 2A-B=1 #

When we solve these concurrent equations, we obtain

# A=2/5, \ B=-1/5 #

Consequently, we have:

# y= e^(2x)(2/5sinx- 1/5cosx)#

Since this is our initial integral's antiderivative, we have:

# int \ e^(2x)sin(x) \ dx = e^(2x)(2/5sinx- 1/5cosx) + c#
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 3

To find the antiderivative of ( e^{2x} \cdot \sin(x) ), you can use integration by parts. Let ( u = \sin(x) ) and ( dv = e^{2x} , dx ). Then, ( du = \cos(x) , dx ) and ( v = \frac{1}{2} e^{2x} ). Applying the integration by parts formula:

[ \int e^{2x} \cdot \sin(x) , dx = -\frac{1}{2} e^{2x} \cdot \cos(x) + \frac{1}{2} \int e^{2x} \cdot \cos(x) , dx ]

Now, we need to integrate ( \frac{1}{2} e^{2x} \cdot \cos(x) ). This can be done by integration by parts again. Let ( u = \cos(x) ) and ( dv = \frac{1}{2} e^{2x} , dx ). Then, ( du = -\sin(x) , dx ) and ( v = \frac{1}{4} e^{2x} ). Applying the integration by parts formula:

[ \int e^{2x} \cdot \sin(x) , dx = -\frac{1}{2} e^{2x} \cdot \cos(x) + \frac{1}{2} \left( \frac{1}{4} e^{2x} \cdot \cos(x) + \frac{1}{4} \int e^{2x} \cdot \sin(x) , dx \right) ]

Now, we have:

[ \int e^{2x} \cdot \sin(x) , dx = -\frac{1}{2} e^{2x} \cdot \cos(x) + \frac{1}{8} e^{2x} \cdot \cos(x) + \frac{1}{8} \int e^{2x} \cdot \sin(x) , dx ]

Solving for the integral, we get:

[ \frac{7}{8} \int e^{2x} \cdot \sin(x) , dx = \frac{1}{2} e^{2x} \cdot \cos(x) ]

[ \int e^{2x} \cdot \sin(x) , dx = \frac{2}{7} e^{2x} \cdot \cos(x) + C ]

Where ( C ) is the constant of integration.

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7